2023
DOI: 10.1007/s11104-023-05946-3
|View full text |Cite
|
Sign up to set email alerts
|

Ensifer meliloti denitrification is involved in infection effectiveness and N2O emissions from alfalfa root nodules

Abstract: Purpose Alfalfa is one of the most valuable forage crops in temperate climate zones. Ensifer meliloti, the endosymbiont of alfalfa, contains all the denitrification genes but the capacity of alfalfa root nodules to produce nitrous oxide (N2O) is not known. In this work, N2O emissions as well as the influence of bacteroidal denitrification on nodulation competitiveness and N2O release from alfalfa nodules has been investigated. Methods Medicago sativa cv. V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Alfalfa root nodules produce N 2 O and Nap has an important role on its release from nodules in response to nitrate and flooding (Pacheco et al, 2023). Recently, a novel strategy to avoid these undesirable metabolic pathways was the screening of S. meliloti strains with spontaneous mutations in napC, which encodes the nitrate reductase structural protein NapC involved in the first step of N 2 O production via the denitrification process.…”
Section: Denitrification Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Alfalfa root nodules produce N 2 O and Nap has an important role on its release from nodules in response to nitrate and flooding (Pacheco et al, 2023). Recently, a novel strategy to avoid these undesirable metabolic pathways was the screening of S. meliloti strains with spontaneous mutations in napC, which encodes the nitrate reductase structural protein NapC involved in the first step of N 2 O production via the denitrification process.…”
Section: Denitrification Pathwaymentioning
confidence: 99%
“…It is unknown whether strain LPU63 codes for the complete denitrification pathway. Recently, it has been shown that the overexpression of the nap operon (coding for the enzymes involved in the first step of the denitrification pathway), promotes nodulation when the host plant develops in a hypoxic environment (Pacheco et al, 2023).…”
Section: Introductionmentioning
confidence: 99%